1987
DOI: 10.1042/bj2420729
|View full text |Cite
|
Sign up to set email alerts
|

The role of ATP in the control of H+-galactoside symport in the yeast Kluyveromyces marxianus

Abstract: Transport of methyl beta-D-thiogalactoside and p-nitrophenyl beta-D-galactoside is shown to proceed through the H+-lactose symporter of Kluyveromyces marxianus. Uptake of these compounds is strongly reduced under anaerobic conditions or aerobically in the presence of antimycin. It is shown that antimycin treatment affects p-nitrophenyl beta-D-galactoside uptake in a similar way as it affects the cellular amount of ATP, suggesting regulation of p-nitrophenyl beta-D-galactoside transport by ATP. Also, manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The lactose transport results (with a K. lactis strain and two recombinant strains of S. cerevisiae) are consistent with those of earlier work by Van den Broek et al (45), who showed that the rate of lactose transport by K. marxianus closely correlated with intracellular ATP levels when these were manipulated in various ways, including preincubation with glucose (to increase ATP) or with antimycin A (to decrease ATP). Also, for the glycerol/H ϩ symport of S. cerevisiae, a short (20-s to 5-min) preincubation of starved cells with glucose increased the V max value by about 30%, with no change in K m (as reported by Lages and Lucas [22]; possible changes in adenylate nucleotides were not examined by these authors).…”
Section: Vol 74 2008 Stimulation Of Zero-trans Active Sugar Uptake supporting
confidence: 90%
“…The lactose transport results (with a K. lactis strain and two recombinant strains of S. cerevisiae) are consistent with those of earlier work by Van den Broek et al (45), who showed that the rate of lactose transport by K. marxianus closely correlated with intracellular ATP levels when these were manipulated in various ways, including preincubation with glucose (to increase ATP) or with antimycin A (to decrease ATP). Also, for the glycerol/H ϩ symport of S. cerevisiae, a short (20-s to 5-min) preincubation of starved cells with glucose increased the V max value by about 30%, with no change in K m (as reported by Lages and Lucas [22]; possible changes in adenylate nucleotides were not examined by these authors).…”
Section: Vol 74 2008 Stimulation Of Zero-trans Active Sugar Uptake supporting
confidence: 90%
“…The depolarization of anoxic cells is often attributed to an insufficient energy supply. This assessment is supported by data showing some correlations between membrane potential and ATP level modulated by low oxygen pressure (15), by inhibitors of energy metabolism (19,27) or imposed by perfusion techniques as in giant alga cells (14). However, these authors noticed a number of circumstances in which this correlation does not hold.…”
Section: Introductionmentioning
confidence: 79%
“…These findings suggest that factors other than ATP are implicated in the regulation of membrane potential under anoxic conditions. It is well established that sugar or amino acid transport in plant cells is driven by pmf' and that ATP fuels this electrogenic process (1,6,20,27), but it is difficult to find concurrent in vivo data on cellular free energy change, pmf generation, and substrate transport. Furthermore, the concept that ATP is the only fuel of these processes has been questioned by several reports on the possible involvement of another H+ secreting system linked to a redox chain with NAD(P)H as electron donor and stimulated by ferricyanide (4,16,21).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, unlike S. cerevisiae , many species have been shown to take up glucose by active transport . For Candida utilis at low glucose concentrations, glucose enters by proton symport, but it enters by facilitated diffusion at high concentrations288, 380. Various Pichia species were also recorded as having both low‐ and high‐affinity uptake systems for glucose34, 98.…”
Section: Transport Into Various Yeast Speciesmentioning
confidence: 99%